Innovation and valuation of Chinese born-global firms - Ruize Cai; Chenyu Zhang; Yiming Xie; Minho Kim (PLoS ONE, 2025)
With the advancement of corporate globalization, an increasing number of small and medium-sized enterprises (SMEs) have leveraged globalized resources to achieve accelerated growth mode that significantly depart from the traditional gradual development trajectories of large enterprises. Notably, the emergence and evolution of born-global (BG) firms have attracted substantial scholarly attention in international business research. This paper studies the innovation and valuation of Chinese born-global (BG) firms, based on dynamic capabilities theory and resource-based view, explores the determinant factors of becoming BG firms, and explores an empirical analysis of changes in the value of BG firms. This paper utilizes the OLS model and panel model, as well as Heckman two-stage, propensity score matching (PSM), and heterogeneity analyzes. We conducted some empirical tests on financial data from 2007 to 2021. The empirical results show that the implementation of the BG mode by enterprises contributes to the growth of corporate value and innovation plays a positive moderating role in this relationship. In addition, the determinant factors for a company to adopt the BG mode are total assets, ownership, and the rate of the largest shareholder. Heterogeneity analysis indicates greater impact on private, foreign, and eastern regional firms. The Heckman two-stage selection model effectively addressed the identification requirements for exclusion restriction variables, while the PSM methodology demonstrated improved covariate balance distributions across matched groups. This dual approach collectively mitigated endogeneity concerns and enhanced the robustness of estimation outcomes. Finally, this study provides business managers with a valuation model for enterprise internationalization, which helps small and medium-sized enterprises choose BG mode to start the internationalization process in their initial stage. Furthermore, this study has significantly enriched the existing literature concerning innovation, corporate value, and equity characteristics of BG firms, while establishing novel theoretical perspectives and methodological avenues for subsequent research investigations.